PERSEPSI, REFERENSI KELOMPOK TERHADAP KEPUTUSAN PEMBELIAN PRODUK HALAL KOSMETIK PADA MAHASISWI FEB UNIVERSITAS MUSLIM INDONESIA - Ratna Dewi; Nurhayati Azis; Muhammad Syafii A.Basalamah (Jurnal Bisnis dan Kewirausahaan, 2023)
This study aims to examine perceptions, reference groups influence the decision to purchase halal product cosmetics at students of the Faculty of Economics and Business UMI Makassar This research design uses quantitative approaches in qualitative, data types, primary and secondary data, questionnaire sampling techniques. The number of respondents was 140 people, with the multiple regression analysis method The results showed that the variables of student perception, group preference towards consumer purchases together had a significant influence on the decision to purchase halal cosmetic products FEB UMI Student Preferences have a significant influence on purchasing decisions and group preferences have a positive and significant effect on purchasing decisions for halal cosmetic products FEB UMI students who are strengthened by attitude, credibility, similarity and strength